SOCIAL COMMUNICATION IN THE DEVELOPMENT OF AGRICULTURE SECTOR - Saefudin, Iing (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article seeks to examine personal and group communication in the development of the agricultural sector. This research uses a qualitative method by extracting data through in-depth interviews and observations. This research found that personal communication and farmers' groups need to be more directed to the development of internal interests. Communication relations are realized not only on social and cultural aspects, but also economic and political aspects. By emphasizing economic and political aspects, the level of welfare of farmers will be more beneficial. This research has the conclusion that the farming community will be more optimal if it is directed at the economic and political aspects so that they will be able to improve their welfare.